The Good fight - Quezon, Manuel Luis (New York : D. Appleton-Century Company, 1946)
Manuel L. Quezon is the President of the Commonwealth of the Philippines.
I. Birth and childhood -- II. Youthful romance and law studies -- III. I join the revolution -- IV. In Manila again -- V. Law practice and public office -- VI. Washington -- VII. Philippine legislation -- VIII. My election as president -- IX. Executive problems -- X. Another visit to the United States -- XI. The Japanese attack -- XII. Corregidor and Bataan -- XIII. Communications with Washington -- Xiv. Through the blockade from Corregidor -- XV. To Australia and the United States
Includes index.
Keywords: AUTOBIOGRAPHY; QUEZON, MANUEL LUIS, 1878-1944